2004
DOI: 10.1007/s10800-004-1759-0
|View full text |Cite
|
Sign up to set email alerts
|

Flow influenced electrochemical corrosion of nickel aluminium bronze ? Part II. Anodic polarisation and derivation of the mixed potential

Abstract: The mixed charge and mass transfer influenced anodic current response of CA 104 nickel aluminium bronze (NAB) is presented as a function of both laminar (rotating disc electrode) and fully turbulent (rotating cylinder electrode) fluid flow. At low values of positive polarisation, the overall behaviour of the freshly polished material in filtered and artificial seawaters is closely related to that of unalloyed copper. The primary anodic reaction in this case is the selective dissolution of the copper component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…The [14]. After initial immersion in each of the electrolytes, it was observed that for a given angular velocity, the corrosion potential, E cor , tended to became more negative with time until a stable potential was achieved.…”
Section: Open-circuit Electrode Potential Vs Timementioning
confidence: 99%
See 1 more Smart Citation
“…The [14]. After initial immersion in each of the electrolytes, it was observed that for a given angular velocity, the corrosion potential, E cor , tended to became more negative with time until a stable potential was achieved.…”
Section: Open-circuit Electrode Potential Vs Timementioning
confidence: 99%
“…In a series of papers by Kear et al [12][13][14][15], oxygen reduction at NAB in aqueous chloride electrolytes was considered. The cathodic polarisation behaviour was examined in fully characterised seawaters (filtered and artificial) using the RDE and the RCE [12].…”
Section: Mass Transport Controlled Current Density Vs Rotation Speedmentioning
confidence: 99%
“…THE NiAl bronze alloy (NAB) is extensively used for propulsion and seawater handling systems [1][2][3][4][5][6] due to the high strength, good fracture toughness, and excellent erosion-corrosion resistance. [1][2][3][4]7] The as-cast NAB is characterized by coarse Widmansta¨tten a phase, nickeliron-aluminum j phases, and island martensite b¢ phase, and the transformation products and their precipitation sequence are complex.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum-bronze is widely used in heat-exchangers. The addition of aluminum to copper increases its corrosion resistance in sea water, sulphuric acid and salt solutions [5]. Alloys with aluminum content up to 8% have completely face-centered cubic (fcc) a structures and good mechanical and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…For Cu-Al alloys, passivation is based on aluminum which has a greater affinity to O 2 than copper, forming Al 2 O 3 [8]. The cathodic and anodic polarization of nickel aluminum bronze was investigated in seawater [2,5]. The results indicated that, the reduction of oxygen dominates the cathodic process and is controlled by the exchange of a single electron.…”
Section: Introductionmentioning
confidence: 99%